Fibroblastic osteosarcoma in a lion (Panthera leo) - L. Leonardi; E. Lepri; S. Nannarone; O. Olivieri; L. Mechelli (Open Veterinary Journal, 2014)
This report describes a case of spontaneous fibroblastic osteosarcoma in the humerus of a lion from a private park in Perugia, Italy. The tumor had an irregular, smooth, brown surface and a generally firm, rubbery consistence with gritty to hard areas interspersed. The mass was poorly vascularized with areas of necrosis at the periphery. The cut surface showed a multilobulated mass that had breached the humeral cortex, with periosteal production of reactive bone. The mass invaded the epiphysis, the synovial membrane, the joint capsule and ligaments. A mild hemorrhagic effusion appeared in the joint space. Clinical signs, gross and histopathologic findings are described in this rare case of a malignant bone tumor.